2001
DOI: 10.1111/j.1572-0241.2001.03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Colonoscopy With Biopsy in The Evaluation of Patients With Chronic Diarrhea

Abstract: Colonoscopy and biopsy is useful in the investigation of patients with chronic diarrhea yielding a histological diagnosis in 31% of patients without a previous diagnosis. Ileoscopy complemented colonoscopy findings in a minority of patients with chronic diarrhea and was essential for a diagnosis in only two patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
4
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 25 publications
7
62
4
5
Order By: Relevance
“…Because from the histological study of these cases that the diagnosis of diseases as the Crohn's disease (6,26) , intestinal tuberculosis (13) , cytomegalovirus infection (20) and microsporidiasis (26) were possible. On the other hand, YUSOFF et al (24) and SILVA et al (21) verified that the microscopical evaluation of patients with chronic diarrhea and normal ileoscopy did not contribute to their patients diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because from the histological study of these cases that the diagnosis of diseases as the Crohn's disease (6,26) , intestinal tuberculosis (13) , cytomegalovirus infection (20) and microsporidiasis (26) were possible. On the other hand, YUSOFF et al (24) and SILVA et al (21) verified that the microscopical evaluation of patients with chronic diarrhea and normal ileoscopy did not contribute to their patients diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggest performing biopsies of the terminal ileum of normal endoscopic aspect in patients with chronic diarrhea and or abdominal pain (3,6,13,20,26) . Because from the histological study of these cases that the diagnosis of diseases as the Crohn's disease (6,26) , intestinal tuberculosis (13) , cytomegalovirus infection (20) and microsporidiasis (26) were possible.…”
Section: Discussionmentioning
confidence: 99%
“…Collagenous colitis (CC) differs from lymphocytic colitis (LC) in that it presents a sub-epithelial collagen band adjacent to the basal membrane, whereas the hallmark of LC is a dense lymphocytic infiltration in the epithelium. The condition is commoner in women, 22 is a frequent cause of an altered bowel habit towards looser stools, 23,24 and is often accompanied by abdominal pain. [25][26][27] The incidence of MC has been reported as 2.6 to 21.0 Kamp et al…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that common causes of chronic diarrhea in the developing countries are bacterial, mycobacterial and parasitic infections. 12 However results of the present study shows that ulcerative colitis is also responsible for considerable number of cases presenting with chronic watery diarrhea. Colonoscopy with biopsy provided the definitive diagnosis in 41% of patients which proves the importance of this procedure as part of the work up in chronic diarrhea while Shah et al 12 found that colonoscopy with biopsy yielded the diagnosis in 31% of their cases.…”
Section: Discussionmentioning
confidence: 85%